2020
DOI: 10.1080/1369118x.2020.1776369
|View full text |Cite
|
Sign up to set email alerts
|

An effective ‘weapon’ for the weak? Digital media and interest groups’ media success

Abstract: The equalization-normalization debate concerns whether the Internet equalizes politics by empowering resource-poor organizations, or whether it further strengthens the position of resource-rich organizations. We address this debate by studying how interest groups' utilization of digital media is associated with their success in influencing news media. We suggest digital media is characterized by the coexistence of old and new media logics that benefit resource-rich and resource-poor groups in different ways. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Gandy, 1982; Berkowitz and Adams, 1990). The finding is also in line with previous studies on interest groups’ media access (Binderkrantz and Christiansen, 2014; Grömping, 2019; Oehmer, 2017; Vesa et al, 2020). However, the finding about the stronger effect of media effort than of insider status must be interpreted with caution, as our data provide a relatively conservative test for the effect of insider status.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Gandy, 1982; Berkowitz and Adams, 1990). The finding is also in line with previous studies on interest groups’ media access (Binderkrantz and Christiansen, 2014; Grömping, 2019; Oehmer, 2017; Vesa et al, 2020). However, the finding about the stronger effect of media effort than of insider status must be interpreted with caution, as our data provide a relatively conservative test for the effect of insider status.…”
Section: Conclusion and Discussionsupporting
confidence: 92%
“…Indeed, studies have found a positive association between media effort and media access in Germany (e.g. Oehmer, 2017), the Nordic countries (Binderkrantz and Christiansen, 2014; Vesa et al, 2020), and among election monitoring groups (Grömping, 2019). However, a study focusing on local environmental organizations in North Carolina found that media effort was not associated with media access when other factors, such as resources, were held constant (Andrews and Caren, 2010).…”
Section: How Media Effort and Insider Status Matter For Media Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…While the literature on digital transformation is growing in several fields, research on the effects of digital innovation in public affairs management is still scattered and almost exclusively focusing on interest groups' use of social media in their direct and indirect lobbying strategies (Brown, 2016; Chalmers & Shotton, 2016; Johansson & Scaramuzzino, 2019; Lovejoy & Saxton, 2012; Van der Graaf et al, 2016; Vesa et al, 2022), with a more limited number of contributions analyzing how technological developments might change interest groups' legitimization (Fraussen & Halpin, 2018) or organizational capacities (Bailard, 2017; Halpin, 2014; Meli & Grefe, 2017; Vromen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%